Performance of Basmati rice as influenced by green manuring and sulphur fertilization - MANDI, SUNIL; SHIVAY, YASHBIR SINGH (The Indian Journal of Agricultural Sciences, 2021)
Basmati rice (Oryza sativa L.) cultivation is mainly confined to the Himalayan foothill belt of Indo-Gangetic plains owing to its specific climatic requirement for its quality. Green manuring and sulphur fertilization play an essential role for sustaining productivity and maintaining grain quality. A two-year field experiment was conducted at the research farm of the ICAR-Indian Agricultural Research Institute, New Delhi, India, during kharif (June-November) 2018-19. The experiment was conducted in a split-plot design with two green manure crops such as dhaincha (Sesbania aculeata), sunhemp (Crotalaria juncea) and control in the main-plot and sulphur fertilization such as 20 kg S/ha to rice, 40 kg S/ha to rice, 20 kg S/ha to wheat, 40 kg S/ha to wheat, 20 kg S/ha both to rice and wheat, 40 kg S/ha both to rice and wheat, and control (no sulphur) in the sub-plots with three replications. Dhaincha green manuring recorded the highest yield attributes with 47 more effective tillers/m2, panicle length by 1.50 cm, panicle weight by 0.21 g, and numbers of filled grains by 7 compared to control. It was also recorded 22% more grain yield and higher monetary returns with a higher B:C ratio of 1.27. Application of 40 kg S/ha both to rice and wheat showed maximum Basmati rice yield attributes, higher productivity, which was statistically at par with 40 kg S/ha to rice. However, from an economic point of view 40 kg S/ha was recorded more monetary returns and average two-year extra-net returns of ₹11.784 × 103/ha than control and higher B:C ratio 1.21. Applying sulphur at 40 kg/ha to Basmati rice is recommended to harvest more yield and fetch additional monetary returns.